The Sexual Violence Criminal Law (TPKS Law) in Preserving the Family in The Maqasid Sharia Perspective - Suwarjin Suwarjin; Aadil Ahmad Shairgojri (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2023)
This study aims to unveil the manifestations of sexual violence in Bengkulu and subsequently elucidate the significance of the Sexual Violence Law in safeguarding families through the lens of Maqasid Sharia. Employing a qualitative library research methodology with a normative-conceptual approach, the investigation reveals two main findings. First, the ratification of the Sexual Violence Law signifies a legal stride to address and protect victims, filling a void in specific legislative provisions. Notably, Bengkulu ranks fourth in sexual violence cases within Sumatra, with perpetrators predominantly known to the victims. However, the region lacks comprehensive psychosocial support, including educational aid, psychological services, reproductive health examinations, and talent development opportunities for child victims. The absence of secure shelters compels social workers to resort to orphanages as an alternative. Second, the urgency of the Sexual Violence Law, viewed through the Maqasid Sharia perspective, aligns with the dharuriyat level, emphasizing the protection of religion (Hifz al-Diin), safeguarding the body and soul (Hifz al-Nafs), ensuring mental well-being (Hifz al-‘aql), and protecting offspring (Hifz al-Nasl). This study sheds light on the necessity of legal provisions in mitigating sexual violence while emphasizing the broader societal and familial dimensions from a Maqasid Sharia standpoint.